Beneficios del coaching como herramienta para mejorar las entrevistas en los procesos de selección de las empresas del sector privado en Colombia (2021)
In this research, the subject related to business coaching and the way in which it can be applied in the interviews applied in the selection processes is addressed, generating added value to the company that chooses to adapt this trend within its processes, this can generate greater productivity when selecting those who will be part of the work team within a company. According to Whitmore, coaching is helping someone to think for themselves to find their own answers, to discover within themselves their potential, in short, to achieve their own goals, both professionally and personally. From this small paragraph we can start the search for benefits that training an interviewer as a COACH can bring us in order to be able to get the most out of the participants in each of the interviews carried out in a selection process; It is about having entertaining interviews, interviews where the candidates do not feel attacked, if not quite the opposite, they feel that it is time to let the coach know that they are the ideal person for the position.